The resurgence of Measles in 2019 - P. V., Chaitanya Varma; Rajkumar, Samitha (International Journal of Contemporary Pediatrics, 2019)
Measles, a highly contagious infection caused by a single stranded RNA Paromyovirus is transmitted through aerosol droplets and contact with nasopharyngeal secretions of the infected patient. The incubation period lasts between 10 and 14 days. The Prodromal phase presents with high grade fever, cough, coryza and conjunctivitis. Punctate blue-white spots on the buccal mucosa called Koplik spots are pathognomic of measles. The typical maculopapular rash appears 3-5 days after the onset of fever. It starts from the neck and spreads down to the lower limbs; it decreases in the same pattern lasting for 5-6 days. The patients are considered contagious 4 days prior to 4 days after the appearance of rash.